Cryolysate of Tumor Cells: From Technology of Its Obtaining up to Creation of Anti-сancer Vaccines - Goltsev , Anatoliy; Gaevska, Yulia; Dubrava, Tetyana; Bondarovych , Mykola; Lutsenko, Olena; Ostankov , Maksym (Problems of Cryobiology and Cryomedicine, 2024)
The possibility of obtaining immune dendritic cells (iDCs) from bone marrow mononuclear cells has been proven by adding granulocyte-macrophage colony-stimulating factor, interleukin-4, and tumor cell cryolysate to the culture as an inducer of their maturation. The source of tumor antigens for obtaining iDCs was a cryolysate of Ehrlich adenocarcinoma cells, which was obtained by 5-fold freeze-thawing. It was established that the differentiation of mononuclear cells into iDCs is accompanied by the loss of the CD14 antigen, the appearance of maturity marker characteristics of these cells (CD83, CD11c antigens) and an increase in the expression of costimulatory molecules (CD80, CD86). The research results enable not only to evaluate the qualitative characteristics of iDCs obtained thereby, but also to outline the prospects of their use in immune correction of oncopathology. Probl Cryobiol Cryomed 2024; 34(3):226–235